Oxidative Stress in Kidney Transplantation: Malondialdehyde Is an Early Predictive Marker of Graft Dysfunction - Fonseca, I (2014)
Background Oxidative stress is one of the most important components of the ischemia-reperfusion process after kidney transplantation (KTx) and increases with graft dysfunction. Methods This prospective study was conducted on 40 consecutive KTx recipients to evaluate time-dependent changes in oxidative stress-related parameters within the first week after KTx and to assess their performance in predicting delayed graft function (DGF=dialysis requirement during initial posttransplant week) and graft function at 1 year. Blood samples were collected before (day 0) and after KTx (days 1, 2, 4, and 7). Total antioxidant capacity, plasma levels of malondialdehyde (MDA), and activities of glutathione peroxidase, glutathione reductase and superoxide dismutase were measured. Multivariable linear mixed and linear regression models, receiver-operating characteristic (ROC), and areas under ROC curves (AUC-ROC) were used. Results At all time points after KTx, mean MDA levels were significantly higher in patients developing DGF (n=18). Shortly after KTx (8–12 hr), MDA values were higher in DGF recipients (on average, +0.16 μmol/L) and increased further on following day, contrasting with prompt functioning recipients. Day 1 MDA levels accurately predicted DGF (AUC-ROC=0.90), with a performance higher than SCr (AUC-ROC=0.73) and similar to cystatin C (AUC-ROC=0.91). Multivariable analysis revealed that MDA levels on day 7 represented an independent predictor of 1-year graft function. Antioxidant enzyme activities were not significantly changed during the study period and were not predictors of 1-year graft function. Conclusions Increased MDA levels on day 1 after KTx might be an early prognostic indicator of DGF, and levels on day 7 might represent a useful predictor of 1-year graft function.